Drought resistance of sugar-cane crop for different levels of water availability in the soil - Barbosa,Fernando da S. (2014)
Soil water availability is the main cause of reduced productivity, and the early development period most sensitive to water deficit. This study aimed to evaluate the drought resistance of the varieties of sugar-cane RB867515 and SP81-3250 during the early development using different levels of water deficit on four soil depths. The experiment was conducted at the Department of Biosystems at Escola Superior de Agricultura "Luiz de Queiroz" (ESALQ/USP) in a greenhouse in soil classified as Oxisol, sandy loam texture (Series "Sertãozinho"). Once exhausted the level of available water in the soil, the dry strength of the studied strains are relatively low. Water balance with values less than -13 mm cause a significant decrease in the final population of plants, regardless of the variety, and values below -35 mm, leads to the death of all plants.